O auxilio-doença no direito brasileiro - Cutait Neto, Michel (2005)
Summary Based on human solidarity, as a set of actions that aims offering social protection to the individuals of the society, keeping whole the values of Well-Being and Social Justice, props of the Social Order, Social Security emerges from the Brazilian judicial law, consolidated in the Social Welfare, Social Assistance and Health. Each one of these services offer certain social protection instruments that could satisfy the consequences generated by certain situations in life, defined as social hazard, ensuring that the society is safe, supported and protected, favoring for each one of the individuals to have ensured his human development with dignity. In this concept, Social Welfare manifests its social protection by means of benefits and services, concrete services offered to the individuals, which are justified as specific instruments of social protection that meet each one of the causes of social hazard that the society faces in the world of life. The consequences of the social hazard of certain situations in life generate needs for the individuals of the society, which dynamically reflect systemic effects not only in the individual sphere, but also in the collective sphere, are acknowledged in many situations, such as for example, in the social hazard of advanced age, death, disability, and so many others that may affect the society. Particularly, given the fundamental social repercussion that disability for working reflects in the society, this work will reveal the reasons why this situation is deserving of the social protection offered by the Social Welfare, instrumented by means of a specific welfare benefit, called Sick Assistance, instructed and ruled by Law No. 8.213/91, and anchored as a direct answer from the Brazilian constitutional provisions. In the study of the welfare benefit of the Sick Assistance, this work will seek to reveal the essential elements in conforming this instrument of social protection, its characteristics, its phatic amplitudes, its causes, its consequences, its purposes, its criticism and all delimitations of its juridical nature of welfare benefit. Thus, in the end, allocated in the core of the Social Security and offered by the Social Welfare, the Sick Assistance benefit appears as a specific instrument that aims ensuring social protection for the social hazard of disability for work, allowing for the protected ones, the individuals, to be able to develop their human condition with dignity, as minimum condition to make concrete the ideals of Well-Being and Social Justice sought by the Social Order and by society.